Climate shocks and climate smart agricultural adoption in Sri Lanka, 2024-2025 - van Asselt, Joanna; Weerasinghe, Krishani; Munasinghe, Dilusha; Hemachandra, Dilini (International Food Policy Research Institute, 2025)
We assess the adoption of climate-smart agricultural (CSA) practices and the role of climate shocks using the BRIGHT Integrated Household Survey data for 2024–2025. • Twenty percent of farmers faced severe climatic shocks, while 40 percent faced more moderate negative shocks. • The largest share of farmers reporting natural shocks lived in the dry zone. • Forty-four percent of farmers were negatively affected by pests and diseases, including 72 .per-cent of oilseed and tuber farmers. • Seventy-four percent of farmers reported that changing weather patterns affect their income. • Forty-one percent of farmers reported that they were currently using at least one climate smart agricultural practice (CSA). • Crop type strongly predicts CSA adoption. Vegetable, pulse, and maize farmers are significantly more likely to adopt CSA practices, with marginal effects indicating increases of roughly 16–17 percentage points. In contrast, rice cultivation is not significantly associated with adoption—im-portant given rice’s dominance in the country. • Adoption levels of CSA practices vary sharply across provinces. Eastern Province shows the highest adoption (66 percent), while Sabaragamuwa records the lowest adoption at just 14 per-cent. • Exposure to climate shocks increases CSA adoption. Experiencing a moderate or severe climate shock in the previous year is associated with a 6–7 percentage point increase in CSA adoption, suggesting that shocks are prompting adaptive responses.